A Single-Arm Phase II Study to Evaluate Efficacy and Safety of First-Line Treatment With DCVAC/LuCa, Standard of Care Chemotherapy and Shenqi Fuzheng Injection in Advanced (Stage IIIB/IV) Non-Small Cell Lung Cancer Patients. (March 2022) - Liu, Qing; Lou, Yanni; Li, Liya; Yang, Guowang; Cui, Huijuan; Cheng, Zhiqiang; Li, Yuan; Liu, Meng; Deng, Chao; Wan, Donggui; Yan, Yongxia; Jia, Liqun
Objectives: To evaluate the efficacy and safety of first-line treatment with a dendritic cell vaccination for lung cancer (DCVAC/LuCa), standard of care chemotherapy and Shenqi Fuzheng injection in patients with advanced (stage IIIB/IV) non-small cell lung cancer. Patients and Methods: Patients with histologically or cytologically confirmed recurrent metastatic or advanced NSCLC (stage IIIB/IV) with wild-type epidermal growth factor receptor (EGFR) or EGFR mutation which does not confer increased tumor susceptibility to EGFR-interacting drugs were recruited. For the treatment period, the first cycle of standard of care therapy (SoC) started 2 to 14 days after the leukapheresis procedure. SoC continued 4 to 6 cycles. DCVAC/LuCa was administered from the second cycle of SoC. DCVAC/LuCa was administered in a 3-week cycle schedule (5 doses) and then in a 6-week cycle schedule. Shenqi Fuzheng injection was administered 3 days before each DCVAC/LuCa administration for a total of 14 daily doses. Patients would undergo disease evaluation by computed tomography (CT) scan every 3 months. The primary and secondary endpoint was efficacy with regard to objective response rate (ORR) and progression free survival (PFS). The safety profile was measured by: incidence, type, and severity of all adverse events (AEs), laboratory abnormalities (blood routine test, urine test, and chemical test), physical status, and vital signs. Qi insufficiency was evaluated by tongue diagnosis and questionnaire survey with "Classification and Determination of constitution in TCM." Results: Twenty-three patients from 3 hospitals who received combination therapy were included. ORR was 34.8% (95% CI:16.4%-57.3%). Median duration of response was 5.51 m (95% CI:2.70-8.32). Median PFS was 10.72 m (95% CI:4.52-16.93), 1-year survival was 77.8%. mOS was 21.97 m (95% CI:13.68-30.25). There was 1 severe AE related to a history of heart disease and there were no adverse events related to DCVAC/LuCa treatment. Qi insufficiency was improved significantly ( P  < .0001) from 41.19 ± 14.58 before treatment to 10.52 ± 16.58 after treatment. Conclusion: DCVAC/LuCa, combined with standard of care chemotherapy and Shenqi Fuzheng injection exhibited good benefit in Chinese patients with recurrent metastatic or advanced (stage IIIB/IV) NSCLC, and also significantly improved Qi insufficiency constitution. There were no related adverse events with DCVAC/LuCa treatment.